A two-level method for elephant flow identification - Junrong YAN; Jingchang YE; Peng PAN (Dianxin kexue)
The high accuracy and low overhead of elephant flows identification have a great meaning on solving the controller's single point of failure problem in SDN traffic management.Aiming at the problem of high overhead of the existing elephant flows identification method,a two-level method for elephant flows identification was proposed which included a suspicious elephant detection algorithm based on TCP write-queue in the first stage and areal elephant detection algorithm based on flow duration in the second stage.During the first stage,the suspicious elephant flows were identified in the end systems to reduce the amount of flows monitored by the SDN controller at the second stage.Analysis and simulation prove that, under the premise of ensuring the accuracy of elephant flow identification, the two-level method for elephant flows identification reduces about 85% overhead of identification compared with sampling identification method.